Ecce humanitas: beholding the pain of humanity - Evans, Brad (Insurrections: Critical Studies in Religion, Politics, and Culture, 2021)
Through a critical exploration of violence and the sacred, Ecce Humanitas recasts the fall of liberal humanism. Brad Evans offers a rich analysis of the changing nature of sacrificial violence, from its theological origins to the exhaustion of the victim in the contemporary world.